Condition index in three size classes of the smooth venus clam Chionista fluctifraga from a commercial fishery in Sonora, Mexico - Chávez-Villalba, Jorge; Arreola-Lizárraga, José Alfredo; Castillo-Durán, Ariaana (Acta Universitaria, 2019)
This study shows the condition index (CI) of the clam Chionista fluctifraga in three different size groups (small <30 mm, medium 30 mm - 40 mm, and large > 40 mm) harvested monthly during one year in a commercial fishery (Sonora, Mexico). Temperature, salinity, oxygen, chlorophyll a, particulate organic and inorganic concentrations were recorded once-a-month at the study site. Significant differences of CI were detected; higher for small clams (26.5 ± 3.4), followed by medium (24.0 ± 3.0) and large clams (20.2 ± 3.0). High and moderate correlations (Pearson) of temperature and CI were observed in small and medium clams. Thus, temperature was the variable affecting CI the most and this was detected during the period corresponding to reproduction and nutrient storage of the species. In relation to these processes, the CI reflected a different nutritional value for each group of clams; high for small, moderate for medium animals, and low for large individuals. This may serve to producers when selecting clams with high condition and planning harvesting.